Influenza-like Illness Exacerbates Pneumococcal Carriage in Older Adults. (30th October 2020) - Miellet, Willem R; van Veldhuizen, Janieke; Nicolaie, Mioara A; Mariman, Rob; Bootsma, Hester J; Bosch, Thijs; Rots, Nynke Y; Sanders, Elisabeth A M; van Beek, Josine; Trzciński, Krzysztof
Abstract: Background: In older adults, pneumococcal disease is strongly associated with respiratory viral infections, but the impact of viruses on Streptococcus pneumoniae carriage prevalence and load remains poorly understood. Here, we investigated the effects of influenza-like illness (ILI) on pneumococcal carriage in community-dwelling older adults. Methods: We investigated the presence of pneumococcal DNA in saliva samples collected in the 2014/2015 influenza season from 232 individuals aged ≥60 years at ILI onset, followed by sampling 2–3 weeks and 7–9 weeks after the first sample. We also sampled 194 age-matched controls twice 2–3 weeks apart. Pneumococcal DNA was detected with quantitative polymerase chain reaction assays targeting the piaB and lytA genes in raw and in culture-enriched saliva. Bacterial and pneumococcal abundances were determined in raw saliva with 16S and piaB quantification. Results: The prevalence of pneumococcus-positive samples was highest at onset of ILI (42/232 [18%]) and lowest among controls (26/194 [13%] and 22/194 [11%] at the first and second samplings, respectively), though these differences were not significant. Pneumococcal carriage was associated with exposure to young children (odds ratio [OR], 2.71 [95% confidence interval CI, 1.51–5.02]; P < .001), and among asymptomatic controls with presence of rhinovirus infection (OR, 4.23 [95% CI, 1.16–14.22]; P < .05). When compared with carriers among controls, pneumococcal absolute abundances were significantly higher at onset of ILI ( P < .01), and remained elevated beyond recovery from ILI ( P < .05). Finally, pneumococcal abundances were highest in carriage events newly detected after ILI onset (estimated geometric mean, 1.21 × 10 −5 [95% CI, 2.48 × 10 −7 to 2.41 × 10 −5 ], compared with preexisting carriage). Conclusions: ILI exacerbates pneumococcal colonization of the airways in older adults, and this effect persists beyond recovery from ILI. Abstract : In this study we have assessed the impact of influenza-like illness (ILI) on pneumococcal carriage in older adults. ILI was associated with persistently elevated pneumococcal abundances. Our findings could explain previously reported risk of pneumococcal disease after viral respiratory infection.